W AKTU TANAM DAN POPULASI TANAMAN JAHE (Zingiber officinale Rosc.) SEBAGAI TANAMAN KEDUA DALAM POLA TANAM BERUNTUN - Joedojono Wiroatmodjo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
This study was designed to find out some cultural practices, i.e. the planting time and plant population, to minimize the yield losses of the second crop in ginger continuous cropping pattern. The pot experimental unit consist of planting time treatment (A) with 3 levels i.e. 1, 2, and 3 months after the harvesting of the first crop, and population treatment (B) with 3 levels i.e. 1, 3, and 5 plants/pot. The result shows that the growth and yield were not affected by the planting time treatment, but affected by the plant population treatment. By increasing the plant population from 1 plant/pot (equivalent to 33 300 plants/ha.) up to 3 plants/pot (equivalent to 99900 plants/ha.), the yield reduced about 27.56% in term of tuber fresh weight, but did not affect the tuber growth. Increasing the plant/ha. is not recommended since the production was appraised in term of tuber fresh weight.